Pharmacokinetics of recombinant human granulocyte colony-stimulating factor in rabbits and mice - Liu Xiu-Wen; Tang Zhong-Ming (Acta Pharmacologica Sinica, 2016)
AIM: To study the pharmacokinetics of recombinant human granulocyte colony-stimulating factor (rhGCSF) in rabbits and mice. METHODS: 125I-rhGCSF was prepared by iodogen method and determined by size exclusive HPLC (SEHPLC). RESULTS: Concentration-time curves after i.v. 125I-rhGCSF in rabbits were best fitted with 2-compartment open model. The alpha and terminal elimination T1/2 were 0.25-0.33 and 3.2-4.6 h, respectively. AUC increased with doses, and Cls and K10 were similar. Tpeak was 0.59 +/- 0.25 h after s.c., and elimination T1/2 was similar to that after i.v. The bioavailability after sc was 1.0. In mice the highest level was found in renal system, the next was bile-enteric system. Levels in lymph nodes, bone marrow, and spleen were approximately equal to or slightly lower than that in plasma, while the levels in brain, fat, and muscles were the lowest. About 68%-86% were recovered in urine and feces. CONCLUSION: Pharamcokinetics of 125I-rhGCSF in rabbits and mice provided a useful index for clinical trial.